Bromotyrosines from the sponges acanthodendrilla sp. and pseudoceratina cf. - Opeyemi Joshua Olatunji (Prince of Songkla University, 2015)
Thesis (M.Pharm. (Pharmaceutical Sciences))--Prince of Songkla University, 2014